2003
DOI: 10.1262/jrd.49.329
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Exposure of Bisphenol A on mRNA Expression of Nuclear Receptors in Murine Placentae Assessed by DNA Microarray

Abstract: Bisphenol A (BPA), a candidate endocrine disruptor (ED), is considered to bind to estrogen receptors and to regulate expressions of estrogen responsive genes. It has also shown evidence of affecting the reproductive, immunological and nervous systems of mammalian embryos. However, the effects of BPA on placentae, a central organ of feto-maternal interlocution, are still unclear. To reveal the mechanisms of BPA effects on placentae in mammals, we compared the mRNA expression of 20 nuclear receptors between plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…The decrease in the number of fetuses in this study might have been caused by the direct effect of BPA on fetuses. In fact, microarray analysis has shown that BPA induces some nuclear receptor mRNAs after they bind to the estrogen receptor [10]. The effects of BPA on cytokine production should be examined at the protein level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in the number of fetuses in this study might have been caused by the direct effect of BPA on fetuses. In fact, microarray analysis has shown that BPA induces some nuclear receptor mRNAs after they bind to the estrogen receptor [10]. The effects of BPA on cytokine production should be examined at the protein level.…”
Section: Discussionmentioning
confidence: 99%
“…A lth ou gh DN A microarray has shown that the mRNAs of some nuclear receptors in the mouse placenta are increased by BPA administration [10], no detailed information is currently available about the effect of BPA on placentation and/or the fate of embryos and neonates. The present study shows the morphological changes in the pregnant uterus during placentation after BPA administration in mice.…”
mentioning
confidence: 99%
“…shown to activate at least nine nuclear receptors in murine placenta, including ERβ in the placenta of only male fetuses (36). BPA at 10 μM can significantly increase drug metabolism via stimulating the human orphan nuclear receptor-mediated transcription in HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…To d e t e r m i n e t h e e f f e c t s o f B P A ( W a k o P u r e Chemicals, Osaka, Japan), pregnant mice were orally administered with BPA (0.02, 2, 200, or 20,000 µg/kg/day; dissolved in olive oil. These doses were based on our previous studies [8,24,25]) in the afternoon (1200 to 1400) from 6.5 to 13.5 and from 6.5 t o 17.5 dpc (8 and 12 times, respectively). Vehicle controls were orally treated with purified olive oil (5 ml/kg) under the same conditions.…”
Section: Preparation Of Embryonic Tissuementioning
confidence: 99%